Using forgery documents during crossing Ukrainian State Border (criminal & administrative liability) - Kuryliuk, Yurii; Fesenko, Oleksandr; Kuryliuk, Andrii (Migration & Law, 2025)
The article examines the theoretical and practical foundations of criminal and administrative liability for the use of forged documents when crossing the state border of Ukraine, and reveals the content and essence of this offence. It is determined that the use of forged documents is the most common method of illegally crossing the state border of Ukraine at border crossing points (control points) across the state border. It is established that this act constitutes the deliberate presentation by a person (a citizen of Ukraine, a foreigner or a stateless person) to an authorised official of the State Border Service of Ukraine at a border crossing point (control point) across the state border, a passport or other document specified by law, recognised by Ukraine, which confirms citizenship, certifies the identity of the presenter, and also gives the right to enter or leave Ukraine, with the aim of obtaining permission to cross the state border of Ukraine. Law and order in the border area is closely linked to the use of forged documents, under the ‘cover’ of which many other illegal activities are committed (illegal migration, including human trafficking, smuggling of goods, spread of terrorism, illegal movement of drugs, weapons, ammunition, as well as legalisation of various criminal elements on the territory of Ukraine, etc.). A significant proportion of such forgeries are detected by border guards precisely when they are used to cross the state border of Ukraine.